2014
DOI: 10.1002/lary.24730
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adult‐onset recurrent respiratory papillomatosis

Abstract: AO-RRP was not associated with previously proposed risk factors for juvenile-onset RRP and may be associated with an increased number of lifetime sexual partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…The mean age of the cohort was 52.8 years (median 54; range 27–91). The majority of the subjects (24 of 27) were male, consistent with the male‐to‐female ratio of the incidence of AO‐RRP described in a previous investigation by our group and others . Multiplex analyses confirmed that 25 out of 27 subjects had a HPV‐positive oral rinse.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The mean age of the cohort was 52.8 years (median 54; range 27–91). The majority of the subjects (24 of 27) were male, consistent with the male‐to‐female ratio of the incidence of AO‐RRP described in a previous investigation by our group and others . Multiplex analyses confirmed that 25 out of 27 subjects had a HPV‐positive oral rinse.…”
Section: Resultssupporting
confidence: 87%
“…One may hypothesize that transmission of HPV may not require oral–genital contact and may result from simple oral–oral contact, possibly even via an intermediary fomite. This concept may be supported by some of our previous epidemiologic data, which demonstrated that although RRP patients have statistically more sexual partners compared to controls, they do not have an increased number of oral sex partners . Similarly, longitudinal European studies have shown no association between oral sex and persistent oral HPV infection, putatively suggesting that any intimate contact—not necessarily only oral–genital contact—may result in virus transmission .…”
Section: Discussionmentioning
confidence: 63%
“…JRRP is associated with infection of the upper airway by human papillomaviruses (HPVs) of the α genus, with infection thought to occur by vertical transmission at birth and with a childhood onset of the lesions (7,8). Indeed, an adult-onset form of this disease also exists (referred to as adult-onset recurrent respiratory papillomatosis) with a similar but usually milder phenotype; in these cases, HPV is probably acquired by sexual transmission (9,10).…”
mentioning
confidence: 99%
“…It is not totally clear how HPV in AoRRP is transmitted, but orogenital sexual transmission might be a causative factor . This is supported by the fact that AoRRP is associated with a higher lifetime number of sexual partners compared to healthy controls …”
mentioning
confidence: 99%